In-Vitro Study of Dipyridamole–Propranolol Interaction in Protein Binding in the Absence and Presence of Nicotine: Dipyridamole-propranolol interaction - Rezaei, Zahra; Khabnadideh, Soghra; Afiatjou, Elham (Iranian Journal of Pharmaceutical Sciences, 2005)
The binding of drugs by plasma proteins is an important phenomenon, because it influences the size of the free fraction of the drugs in plasma. In this study the influence of dipyridamole (DP) on the protein binding of propranolol (PL) and PL on the protein binding of DP were studied alone and in the presence of nicotine (NC). The equilibrium dialysis was employed for protein binding studies. Results showed that DP (10 μg/ml) increased the protein binding of PL (1-40 μg/ml) by 4.1%, and PL(30 μg/ml) decreased the protein binding of DP (1-30 μg/ml) by 3.7%. NC (2 μg/ml) did not have any influence on the protein binding of PL and DP. Therefore, coadministration of PL and DP may cause an alteration in their pharmacological effects, but cigarette smoking possibly does not change protein binding of PL and DP.